Cytotoxic effects of Euterpe oleraceae fruit oil (acai) in rat liver and thyroid tissues - Marques, Eduardo de Souza [UNESP]; Froder, Juliano Gabriel [UNESP]; Oliveira, Patricia Rosa de [UNESP]; Perazzo, Fabio Ferreira; Pires Rosa, Paulo Cesar; Mascarenhas Gaivao, Isabel O'Neill de; Camargo Mathias, Maria Izabel [UNESP]; Maistro, Edson Luis [UNESP] (Soc Brasileira Farmacognosia, 2019)
Euterpe oleracea Mart., Arecaceae, fruit (acai) presents considerable potential for the development of new medicines due to its phytochemical composition and antioxidant activity. More recently, special attention has been given to the pharmacological potential of the fruit's oil. This study analysed the histological and histochemical effects of different dosages of acai oil on rat's liver and thyroid cells, in order to evaluate its cytotoxic potential after administration for consecutive days. Male Wistar rats were treated with the acai oil by gavage at doses of 30, 100 and 300 mg/kg, for 14 days, within a 24 h interval. Liver and thyroid fragments were collected for histology (hematoxylin and eosin) and histochemistry analysis (blue of Nilo (lipids), Baker (lipids), bromophenol blue (protein), PAS (polysaccharides)). The results showed that animals exposed to acai oil presented alterations in the liver cells, where the integrity of the liver tissue was increasingly lost as the acai oil doses increased. Nuclear pyknosis was observed in several hepatocytes, evidencing the occurrence of cell death. Alteration in the amount of lipids, polysaccharides, vacuoles in the cytoplasm, and proliferation of Kupffer cells were observed in histochemical analyzes. As for the thyroid of the treated rats, alterations were observed in the size of the follicular lumen and also in the connective tissue found between the follicles. Under the experimental conditions employed in the present study, the cytotoxicity observed in this work is worrying, specially considering the liver, when frequent or continuous damage could lead pathological disorders in this organ. (C) 2019 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda.
Keywords: Acai oil; Thyroid cytotoxicity; Liver cytotoxicity; Acai cytotoxicity